2019
DOI: 10.7717/peerj.7837
|View full text |Cite
|
Sign up to set email alerts
|

A prognostic nomogram for overall survival in male breast cancer with histology of infiltrating duct carcinoma after surgery

Abstract: Objective The study was designed to construct and validate a nomogram for predicting overall survival (OS) of male breast cancer (MBC) patients with infiltrating duct carcinoma (IDC). Methods The cohort was selected from the Surveillance, Epidemiology, and End Results (SEER) database between January 1, 2004 and December 31, 2013. Univariate and multivariate Cox proportional hazard (PH) regression models were performed. A nomogram was develo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 34 publications
3
8
0
Order By: Relevance
“…Previous studies have demonstrated the importance of menopausal status and age in breast cancer assessment. 4,11,15 In our research, the malignancy rate of patients older than 60 years was higher than that of younger patients. Similar results were reported by Oligane et al, 4 who found that patients younger than 50 years had a lower malignancy rate.…”
Section: Figurementioning
confidence: 43%
See 1 more Smart Citation
“…Previous studies have demonstrated the importance of menopausal status and age in breast cancer assessment. 4,11,15 In our research, the malignancy rate of patients older than 60 years was higher than that of younger patients. Similar results were reported by Oligane et al, 4 who found that patients younger than 50 years had a lower malignancy rate.…”
Section: Figurementioning
confidence: 43%
“…20,21 It has been successfully used in the field of breast cancer to predict neoadjuvant efficacy, disease-free survival, lymph node metastasis and the malignancy risk of calcifications in breast cancer patients. 15,[22][23][24][25][26][27] Our results showed that the nomogram can also be used to individually predict malignancy risk for amorphous calcifications, and we suppose that it is better than assess all the amorphous calcifications into BI-RADS 4B only.…”
Section: Figurementioning
confidence: 76%
“…In our study, age at diagnosis, pathological grade, extent of disease, marital status, the administration of surgery and presence of previous primary malignancy were identified to be independent prognostic factors for CSS in PSCC patients. Previous studies have reported that age, tumor stage, extent of disease and the administration of surgery were significantly associated with tumor prognosis in many cancer types (23,24). To our knowledge, those patients who were older, poorly differentiated, metastatic, and not surgically resected were bound to have a poor prognosis.…”
Section: Discussionmentioning
confidence: 70%
“…Nomograms have been successfully established to predict the survival of many tumor types and are considered a more accurate model than the 7th AJCC staging system [26][27][28]. To the best of our knowledge, no nomogram has been established to predict the survival of patients with adenocarcinoma in villous adenoma.…”
Section: Discussionmentioning
confidence: 99%